Value of Multiple Sleep Latency Test Periods and Clinical Correlation - Ibrahim Oztura (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2013)
Aim:Patients with complaints excessive daytime sleepiness were evaluated with Multiple Sleep Latency Test (MSLT) electrophysiological findings and researched narcolepsy symptoms like nightmare, hallucinations, cataplexy in this study. Material and Method: To study 26 patients were admitted retrospectively with complaints of excessive daytime sleepiness at Dokuz Eylul University Faculty of Medicine Sleep Clinic in the dates December 2009- December 2010. Cases of narcolepsy symptoms (hallucinations-nightmare-cataplexy) and MSLT were evaluated together. The onset of REM sleep (SOREM) was counted, than SOREM (+) and SOREM (-) patients’ sleep latency and narcolepsy symptoms were compared. All data were analyzed with SPSS 20.0. Results: The mean sleep latency assessed sleep latencies, gradually widening towards the end of the first sleep period, and it has been observed to be statistically significant(p:0.007). Conclusion: The mean sleep latency assessed sleep latencies, gradually widening towards the end of the first sleep period, and it has been observed to be statistically significant(p:0.007) and we thinked that it can be decreased of need to sleep during nap periods. [Cukurova Med J 2013; 38(4.000): 712-718]